Interferensi Gramatika Maharah Kitabah dan Penyebabnya Pada Mahasiswa Pascasarjana UIN Sunan Kalijaga - Muliansyah, Ariadi; Baroroh, R Umi (Arabiyatuna: Jurnal Bahasa Arab, 2020)
The purpose of this research is to find out the forms of grammatical interference that occur in graduate students of UIN Sunan Kalijaga. Interference is a language disorder that often occurs for language learners. Interference often occurs in all four language skills included in writing skills. Without realizing it, in writing scientific works students still often experience the first language interference, especially in the grammatical field. This research is a qualitative research with descriptive research type. The results found in this study indicate that the grammatical interference still occurs in the writing of graduate students of UIN Sunan Kalijaga. Researchers found 11 grammatical interference with details, 1 interference in the use of isim maushul, 5 interferences in making idahafah, 4 interferences in the use of fi’il (morphology), and 1 interference in the use of hurf.